Pengaruh Kualitas Pelayanan Dan Produk Kredit Multiguna Terhadap Kepuasan Nasabah Kredit Pada PT. Pembangunan Daerah Bali Cabang Utama Denpasar - Ayunda Putri, Anak Agung; Nurcahya, I Ketut (E-Jurnal Manajemen, 2014)
Determining the effect of the quality of services and Multiguna Credit Product simultaneously and partially on credit’s customer satisfaction in PT. Bank Pembangunan Daerah Bali, Denpasar main branch were the purpose of this study. The data analysis technique used is multiple linear regression analysis techniques. 100 respondents were selected using purposive sampling technique. Independent variable examined was the quality of services and Multiguna Credit Product. The results showed that the quality of services and Multiguna Credit Product simultaneously and partially positive and significant effect on credit’s customer satisfaction in PT. Bank Pembangunan Daerah Bali, Denpasar main branch. The results of this study provide practical implications that PT. Bank Pembangunan Daerah Bali, Denpasar main branch need to improve the service system especially the computerized system and service facilities. Multiguna Credit Product need improvement especially on promotion and product innovation to achieve the satisfaction of credit’s customer. Keywords :  quality of service, Multiguna credit product, and credit’s customer satisfaction
Keywords: quality of service, Multiguna credit product, and credit’s customer satisfaction